1998
DOI: 10.1016/s0022-5347(01)63937-5
|View full text |Cite
|
Sign up to set email alerts
|

Burns to the Genitalia and the Perineum

Abstract: Conservative management of perineal and genital burns is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 2 publications
2
50
0
2
Order By: Relevance
“…Michielsen et al 4 reported a retrospective review of 87 male and 30 female patients suffering genital burns who were treated at the Burn Center of the Academic Surgical Center Stuivenberg between 1981 and 1995. The mean patient age was 32 years, mean TBSA was 21% and burn injury was most commonly a result of scalding (55%).…”
Section: Mcdougal Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…Michielsen et al 4 reported a retrospective review of 87 male and 30 female patients suffering genital burns who were treated at the Burn Center of the Academic Surgical Center Stuivenberg between 1981 and 1995. The mean patient age was 32 years, mean TBSA was 21% and burn injury was most commonly a result of scalding (55%).…”
Section: Mcdougal Et Almentioning
confidence: 99%
“…The mean patient age was 32 years, mean TBSA was 21% and burn injury was most commonly a result of scalding (55%). Michielsen et al 4 categorized their patients into scald , flame or other. Scald burns were most often caused by hot liquids or steam and associated with lower TBSA burns, whereas flame burns were associated with smoke inhalation and greater TBSA, resulting in deep, extensive burn injury.…”
Section: Mcdougal Et Almentioning
confidence: 99%
See 3 more Smart Citations